Analisisi Kemampuani Berpikiri Kritisi Matematis iPesertai Didiki Kelas VIII SMPINegeriI13 PadangiTahuniPelajaran 2018/2019 - YUSTIKA . (Departemen Matematika, 2019)
iThe irnportance oficriticalithinkingiinitheiera of the industriallrevolution 4.0, urging educationiis able to prepare generations of critical thinkers to adapt to a challenging life in the future. The reality in Indonesia is found thatistudents' rnathernatical criticalithinkingiskills areistillirelativelyilow. The purpose of thisistudy was toidescribe the level of rnathernatical critical thinking ability of students in class VIIIiof SMP Negerii13iPadang in 2018/2019 Acadernic Year. The criticalithinkingiindicators used according to Facione areiinterpretation, ianalysis, evaluation, andiinference. This researchiis a descriptive qualitative research. Subject selection is done byipurposiveisarnpling. Datairetrieval is done byiobserving, givingitests, andiinterviews. Basedion the resultsiofidataianalysis, it wasiconcluded that the level of rnathernaticalicriticalithinking ability ofistudents in class VIII.1 of SMPN 13 Padangiin the 2018/2019 acaderniciyear was rnoderate, arnounting to 63.39%. Thisiis dueito theilackiofiunderstandingiof students'iconcepts andithe lack ofitraining of studentsito think critically duringilearning and iniexercises. Key words- Analysis, Critical Thinking Skills